Effects of compost, biochar and manure on carbon mineralization of biogas residues applied to soil. (March 2016) - Coban, H.; Miltner, A.; Centler, F.; Kästner, M.
Summary: Biogas residues contain microbial biomass, which contributes to the formation of soil organic matter. Whether the potential of biogas residues to increase soil organic matter can be enhanced by co‐application with compost, biochar or manure is unknown, however. The aim of this paper is to evaluate the effects of co‐amendment on the mineralization of biogas residues, carbon dioxide emissions and the carbon flow within the microbial food web. We determined the fate of 13 C‐labelled microbial biomass present in biogas residues applied together with compost, biochar and manure to soil, by analysing CO2 and biomarker phospholipid fatty acids. Although the rate of mineralization constant of the slowly degrading carbon pool was not affected by co‐amendments, co‐amendment with manure resulted in a larger rate of mineralization constant of the readily degrading carbon pool of biogas residues. The incorporation of carbon was mainly to Gram‐negative biomass and was the smallest with manure co‐amendment, which indicated differences in bioavailability of the carbon source. Highlights: It is unknown whether the increase in soil organic matter by biogas residues can be enhanced by co‐amendment. This paper evaluates the effects of co‐amendment on the fate of biogas residues. The total amount of mineralized carbon derived from biogas residues was not affected by co‐amendment. Co‐amendment is neither beneficial nor detrimental to soil organic matter formation.